(untitled) (Eurasian Scientific Herald, 2022)
This article is about studying the ethnocultural life of Gypsies living in Surkhandarya region. The author relies on ethnographic data and based on available scientific literature analyzed the problem and studied the existing specific aspects of the issues of studying the ethnoculture of the Gypsies of the Surkhan oasis. In addition, in the article, the researcher compares the life of the Gypsies in the last century with the life of the present day